THE MODELLING OF THE MASS-METALLICITY RELATION FOR THE LOCAL GROUP DWARF GALAXIES - Ryabova, M. V.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
We present results of modelling of the mass-metallicity relation for the Local Group dwarf spheroidal (dSph) galaxies. In this work, we use a single-zone chemo-dynamical model. Our model is based on the scheme suggested by C. Firmani and A. Tutukov (1992). The behaviour of the dark-to-visible mass ratio has been taken from M.-M. Mac Low & A. Ferrara (1998). We have considered two classes of models: open and closed. The obtained mass- metallicity relation for the open model shows that the galaxies can be divided into two distinct classes: low-mass (Mtot < 108Msun) and high-mass (Mtot > 108Msun) groups which agrees with observation data.